Cyber Muslims: Mapping Islamic Digital Media in the Internet Age - Khariroh, Riri (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
This new book is a study of Islam in the digital world, containing a collection of scientific articles written by 16 scholars about the increasingly interesting and complex phenomena of the global Islamic world. Most of the authors teach at various universities in the United States and Canada (North America), and the editor of this volume is Robert Rosehnal, Professor in the Department of Religion Studies and Founding Director of the Center for Global Islamic Studies at Lehigh University, Pennsylvania, USA. This interdisciplinary volume highlights cutting-edge research with unique perspectives and new insights into the evolving Islamic cyber landscape, presenting case studies from multiple geographic and cultural locations, and multiple languages â€‹â€‹(Arabic, Persian, Indonesian and Spanish). The main sources of the authors, the analysis and interpretation they use is digital multimedia technology. These â€œvirtual textsâ€ include websites, podcasts, blogs, Twitter, Facebook, Instagram, YouTube, online magazines and discussion forums, and religious apps. Websites and social media platforms are living â€œtextsâ€ that are constantly evolving, shrinking, changing, and even disappearing, leaving no trace. In this sense, this book needs to be seen as a portraitâ€”or, rather, a screenshotâ€”of the complex and deformed cyber world of Islam at some point in its ongoing evolution. This book explores widely the digital expression of various Muslim communities in cyberspace, or iMuslims, related to the world of imams, clerics, and Sufis, feminists and fashionistas, artists and activists, spiritualists and online influencers. Several articles map the diversity and vibrancy of Islamic digital media against the backdrop of broader social trends in particular hot issues affecting Muslims living in Western countries: racism and Islamophobia, gender dynamics, celebrity culture, identity politics, and fashions of piety, and changing religious practices. The case studies presented in this book cover a wide cultural and geographical area, namely Indonesia, Iran, the Arab Middle East, and North America.